Increased production of beta-1,3 glucanase and proteins in Bipolaris sorokiniana pathosystem treated using commercial xanthan gum - Castro, Osvair L. [UNESP]; Bach, Erna E. [UNESP] (Elsevier B.V., 2004)
Barley plants (cultivars Embrapa 127, 128 and 129) treated with xanthan gum, and with different time intervals between the administration of the inducer and the pathogen, demonstrated induction of resistance against Bipolaris sorokiniana. Induction was shown to have local and systemic action. In order to prove the resistance effect, biochemical analyses were performed to quantify proteins and the enzymatic activity of beta-1,3 glucanase. Results demonstrated that barley plants treated with the inducer, showed an increase in the concentration of proteins, as well as in the activity of the enzyme beta-1,3 glucanase, when compared with the extract from healthy plants. In infected plants, protein concentrations decreased and enzymatic activity was lower than in healthy plants. Results suggest that barley plants treated with xanthan gum developed mechanisms responsible for induced resistance, which are still unknown. The most important macromolecule in the defense mechanism was demonstrated to be PR-protein, due to its accumulation and concentration of proteins. However, it may not be the only macromolecule responsible for the resistance effect. (C) 2004 Elsevier SAS. All rights reserved.
Keywords: barley; Bipolaris sorokiniana; proteins; beta-1,3 glucanase; induction protection